Nursing interventions for fall prevention in hospitalized aged people: integrative review - Mayara Muniz Peixoto Rodrigues; Rafaella Felix Serafim Veras; Maria das Graças Melo Fernandes; Maria de Lourdes de Farias Pontes; Lidiane Lima de Andrade; Kamyla Félix Oliveira dos Santos; Jacira dos Santos Oliveira (Universidade Federal do Ceará, 2023)
Objective: to identify nursing interventions for fall prevention in hospitalized aged people. Methods: integrative review developed on the Web of Science, MEDLINE/PubMed, SCOPUS, CINAHL and LILACS databases using the PICo strategy with controlled descriptors and their combinations using the Boolean operators AND and OR. Studies addressing interventions to prevent falls in aged people in the hospital setting were included, without geographical or language limitation, from 2004 with the creation of The World Alliance for Patient Safety. Three reviewers worked on the citations, using EndNote basic and Rayyan, reaching a final sample of 20 studies. Results: 202 nursing interventions were identified for fall prevention in hospitalized aged people, categorized into six domains of the Nursing Interventions Classification (Physiological: basic; Physiological: complex; Behavioral; Safety; Family; Health Systems). Conclusion: nursing interventions were identified for the prevention of falls in hospitalized aged people, which provides subsidies for the construction of care protocols and improvements in care. Contributions to practice: the results allow nurses to prevent the occurrence of falls, putting into practice consistent scientific findings from the planning of actions to the execution and reassessment of results with the team.